On the Fauna of Gamasid Mites of the Genera Anystipalpus and Antennoseius (Mesostigmata, Ascidae) of the Eastern Ukraine - Trach, V.A. (Вестник зоологии, 2013)
The local fauna of mites of the genera Anystipalpus and Antennoseius in “Streltsovskaya steppe” branch of Lugansk Nature Reserve was studied. The aspects of phoresy mites on carabids and the quantitative data of phoresy are reviewed. 334 specimens of 36 carabid species were examined. Seven species of mites of these genera (Anystipalpus livshitsi, A. stepposus, Antennoseius bullitus, A. dungeri, A. kamalii, A. pannonicus, A. ponticus) were found on 16 species of carabids. A. kamalii are recorded for the first time for Europe and Ukraine. A. livshitsi collected from 13 species of carabids, other species of mites were found on 1–6 species of beetles. The index of dominance of certain species of mites is 0.2–81.4 %, the index of occurrence — 0.4–20.6 %. The maximum values of the intensity of mites invasion (phoresy) was observed for A. livshitsi (8.0) and A. bullitus (8.2). Up to 72 mite specimens were observed on one specimen of beetle. Simultaneous phoresy (synphoresy) of mites of these genera are registered for the first time. It is suggested that mites are weakly associated with certain taxa of ground beetles, and more associated with certain size group of carabids and probably with their habitats.